2011
DOI: 10.1080/13636820.2010.549948
|View full text |Cite
|
Sign up to set email alerts
|

Developing a framework for communication management competencies

Abstract: Using a hierarchical needs assessment model developed by Hunt we identified the essential competencies of communication management practitioners for the purpose of curriculum development and selection. We found that the underlying values of the profession were embodied in two superordinate goals. Six major competencies were identified, which were defined by further sub-competencies. In addition, four main personal attributes were rated as important to professional performance. While we found high levels of agr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 57 publications
0
33
0
1
Order By: Relevance
“…Of these, respondents identified writing as the core skill with 'thorough knowledge of the company and of business principles' nominated as 'essential ' (p.203). These two skills and knowledge areas are identified frequently in the literature as very important to communication practitioners (Oughton, 2004;Brown and Fall, 2005;McCleneghan, 2006;Jeffrey andBrunton, 2011 andSha, 2011). Another key skill area identified in the literature is that of critical thinking or its related terms -problem solving, analytical skills or strategic thinking.…”
Section: Role Of Practitionersmentioning
confidence: 99%
See 3 more Smart Citations
“…Of these, respondents identified writing as the core skill with 'thorough knowledge of the company and of business principles' nominated as 'essential ' (p.203). These two skills and knowledge areas are identified frequently in the literature as very important to communication practitioners (Oughton, 2004;Brown and Fall, 2005;McCleneghan, 2006;Jeffrey andBrunton, 2011 andSha, 2011). Another key skill area identified in the literature is that of critical thinking or its related terms -problem solving, analytical skills or strategic thinking.…”
Section: Role Of Practitionersmentioning
confidence: 99%
“…This is probably the most appropriate definition for use in this study as it effectively distinguishes competencies from skills, knowledge and personal attributes. Jeffrey and Brunton (2011) highlight the advantage of studying competencies over roles as; "roles outline tasks and responsibilities in the job description (and) in today's dynamic workplace these same roles are likely to change frequently. In contrast, competencies are the underlying foundational abilities that are integral to successfully carrying out the tasks and responsibilities, and thus remain a stable blueprint for practice over time" (p. 60).…”
Section: Competenciesmentioning
confidence: 99%
See 2 more Smart Citations
“…It also confirmed that much work is still needed to improve professional practice in Europe, since "As professional communicators are moving from mostly operational to more managerial, educational and reflective levels, building competencies and skills is the next big challenge both for individuals and organisations (Tench, 2012;Sha, 2011;Jeffrey & Brunton, 2011)" (Zerfass, Verçiç, Verhoeven, Moreno & Tech, 2012: 77).…”
Section: Literature Review and The Ecm-european Communication Monitormentioning
confidence: 93%